Influenced : the impact of social media on our perception - Boxer Wachler, Brian S. (Rowman & Littlefield Publishing Group, 2022)
"This book unpacks what happens to our brains and our behaviors each time we click 'Like' or even just scroll for new content on social media. Through interviews with top influencers, the latest studies, and pop-culture anecdotes, and Dr. Boxer Wachler's own expertise as both a scientist and an influencer himself, he reveals how influence works"--